PENDIDIKAN KESENIAN DALAM PEMBANGUNAN KARAKTER BANGSA - K Kasiyan (Jurnal Cakrawala Pendidikan, 2002)
The aim ofeducation in art in the context ofthe public schoolin Indonesia is paradigmatically oriented more to the perspective ofunderstanding "art as an educational medium" (or education through art) in the sense that all activities or processes of making art can be made to function as effective media to help the optimum growth and development ofall the individual learner's potentials in the dimension of the "emotionality/sensibility" domain (or emotional quotient). Therefore, education in art at public school belongs to the category of "value education".However, that strategic aim ofeducation in art at public school in Indonesia has all this time been relatively alienated in its existence in comparison with other fields ofscience because it is not considered so important and even merely a complementary field. This is due to the educational system in Indonesia, whose paradigm has all this time been supported more by the spirit of scientific and technological development only to meet the demand of the jargon of national development and  modernization projects. That format of educational policy and politics has imperceptibly brought about various cultural crises and pathology in society, ofwhich one indicator is the steadily drying humanistic values in society. Therefore, it is proper that in implementing the idea ofeducational reformation, which has become so much the concern these days, the dimension ofvalue education -including that with art as basis- is framed in the national educational system more proportionally andin a more balanced way with other fields with science and technology as basis so that there can be more balance between the "intellectuality" and "emotionality/sensibility" domains or between the "rationality" and "irrationality" domains in the individual leamer, which further can be hoped to bring closer the achievement of the idealized quality of the complete Indonesian person.